Chloe Leline: capstone - Leline, Chloe artist (Colorado State University. Libraries, 2023)
The artist's statement: I grew up hearing people tell my mother "You've got a great eye" as they would walk through whatever space was currently our home. I grew up seeing my dad draw on the back of the receipt at every restaurant we'd go to. As time passed I saw myself in them. Doodling on my math tests and helping my friends hang posters and paintings up in their room because they liked the way I worked with the layout. Now I'm a graphic designer. I used to feel like I couldn't call myself an artist because there's not one solid theme in my artwork or one specific style that shines through in my design. What I once saw as a weakness, I realize now is what makes me good at my craft. I am able to mold myself and my art to fit the job that needs to be done. One of my professors once told me "Everything you make is your style of art because you are the one that made it. " One thing that stays true to each project I do is my process. Even if the work I'm doing will result in a digital product, I always start with pen to paper. I like to treat my sketchbook as a scrapbook, filling it with bits and pieces of anything and everything, glued and taped in alongside my sketches to bring the whole thing to life. That's how I like to work, and now I understand that the process holds just as much artistry as the designs that result from it. I wasn't one of those people who always knew what they wanted to be when they grew up, it changed often, jumping from chef to fashion designer. Still, all of my interests have revolved around the act of creation. Even though graphic design can be more technical, there's still creative freedom to it. I believe that the key to a good designer is to be able to find a balance between them. If I'm not pushing myself and growing as a designer with each chance I get, I'm doing it wrong.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design